Supervised exercise training in patients with cancer during anthracycline-based chemotherapy to mitigate cardiotoxicity: a randomized-controlled-trial - Schneider, Caroline; Ryffel, Christoph; Stütz, Laura; Rabaglio, Manuela; Suter, Thomas M.; Campbell, Kristin L.; Eser, Prisca; Wilhelm, Matthias (Frontiers in Cardiovascular Medicine, 2023)
Exercise training (ET) has been shown to mitigate cardiotoxicity of anthracycline-based chemotherapies (AC) in animal models. Data from randomized controlled trials in patients with cancer are sparse.Patients with breast cancer or lymphoma receiving AC were recruited from four cancer centres and randomly assigned to three months supervised ET. Primary outcome was change in left ventricular global longitudinal strain (GLS) from baseline (before AC) to post AC (AC-end) compared between the EXduringAC group, who participated in an exercise intervention during AC including the provision of an activity tracker, and the control group EXpostAC, who received an activity tracker only. Secondary outcome parameters were changes in high sensitivity Troponin T (hsTnT), NT-pro-brain natriuretic peptide (NT-proBNP), peak oxygen consumption (peak VO 2 ) and objectively measured physical activity (PA) during this same time-period. All assessments were repeated at a 12-week follow-up from AC-end, when also the EXpostAC group had completed the ET, that started after AC. In exploratory analyses, robust linear models were performed to assess the association of PA with changes in echocardiographic parameters and biomarkers of LV function.Fifty-seven patients (median age 47 years; 95% women) were randomized to EXduringAC (n=28) and EXpostAC (n=29) group. At AC-end, GLS deteriorated in both study groups (albeit insignificantly) with 7.4% and 1.0% in EXduringAC (n=18) and EXpostAC (n=18), respectively, and hsTnT and NT-proBNP significantly increased in both groups, without difference between groups for any parameter. Change in peak VO 2 (-1.0 and -1.1 ml/kg/min) at AC-end was also similar between groups as was duration of moderate-to-vigorous PA (MVPA) with a median of 33 [26, 47] min/day and 32 [21, 59] min/day in the EXduringAC and EXpostAC group, respectively. In the robust linear model including the pooled patient population, MVPA was significantly associated with a more negative GLS and lesser increase in hsTnT at AC-end.In this small scale RCT, supervised ET during AC was not superior to wearing a PA tracker to mitigate cardiotoxicity. The dose-response relationship between PA and cardioprotective effects during AC found in our and previous data supports the notion that PA should be recommended to patients undergoing AC.